2018
DOI: 10.1596/29819
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Cost-Effectiveness Analysis of Tobacco Price Increases in the Kyrgyz Republic

Abstract: WHO currently recommends that countries increase the excise tax rate for tobacco to 75 percent (WHO 2015). 1 High excise taxes on tobacco products, however, continue to be underused in LMICs, despite the high-and in many cases rising-prevalence of smoking. Introducing or increasing taxes on tobacco items has raised concerns about the impact of such increases on low-income consumers (i.e. the distributional impact). Indeed, perceived regressivity of tobacco taxation has been used as one of the main arguments ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Evidence shows that tobacco taxation policies play an important role in achieving significant health outcomes in low-and middle-income countries (LMICs), especially among the poor, as well as help reduce poverty [44][45][46][47][48][49]. In 2012, Powell et al had shown that pricing tools could be considered and evaluated as potential policy tools to pursue health risk factors [50], which were consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence shows that tobacco taxation policies play an important role in achieving significant health outcomes in low-and middle-income countries (LMICs), especially among the poor, as well as help reduce poverty [44][45][46][47][48][49]. In 2012, Powell et al had shown that pricing tools could be considered and evaluated as potential policy tools to pursue health risk factors [50], which were consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Many countries have implemented plans to introduce taxes on Sugar-Sweetened Beverages (SSBs) and foods high in salt, fat, and sugar [29][30][31][32][33][34][35][36][37]. Also, tobacco taxation policies have been implemented to improve health in many countries [38][39][40][41][42][43][44]. In this regard, tobacco taxes have caused a 12% reduction in sales in Turkey between 2008 and 2012, and a 50% reduction in sales in France between 1990 and 2005 [45].…”
Section: Introductionmentioning
confidence: 99%